Hubungan Waiting Time Dengan Kepuasan Pasien Prioritas 3 di Instalasi Gawat Darurat Rumah Sakit Tingkat II Robert Wolter Mongisidi Manado - Yana Lajali; Suwandi I. Luneto; Faradilla M. Suranata (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
The Emergency Department (ED) is a unit in a hospital specializing handles patients in emergency conditions quickly and effectively with a predetermined waiting time. Waiting Time is one form of service that many people complain about in the emergency room and causes patient dissatisfaction. When the waiting time can managed properly according to hospital service standards, the patient satisfaction and trust will increase. The purpose of this study was to determine the correlation between Waiting Time and the Satisfaction of third priority patients in the Emergency Room of Tk II Robert Wolter Mongisidi Hospital Manado. This research design with cross-sectional approach. The sample was taken based on the number of third priority patient respondents as many as 42 people using Purposive Sampling. The results of this study showed the most of the waiting time was in accordance with the standard with 27 respondents (64.3%) and most of the respondents who were satisfied were 36 respondents (85.7%). Chi square statistical test results obtained p-value = 0.016 <0.05 which shows there were a correlation between waiting time and the satisfaction of third priority patient in the emergency room at Robert Wolter Mongisidi Hospital Manado. The conclusion of the study there is a the waiting time and the satisfaction of third priority patient in the emergency room of the Robert Wolter Mongisidi Hospital, Manado City was correlated.